Analysis Of Fire Protection And Countermeasures System At Limo Campus Of UPNVJ In 2020 - Situmeang, Lundu Sanada (Health Safety Environment, 2020)
Background: The aim of this study was to analyze active and passive fire protection systems along with countermeasures in each building at Limo Campus, compare to applicable regulations (Minister of Public Workers Regulation No.26 / PRT / M / 2008 and the National Fire Protection Association). This research used an observational descriptive study designThis study found that an element of the passive fire protection system at Limo Campus which was door, did not meet the requirement standards. In addition, no fire emergency response and training has been conducted. The building had no emergency respone procedure as well. A fire protection and control system that is in accordance with standards is needed to reduce fire hazards, such as changing doors, adding fire alarms and conducting training on fire.